2020
DOI: 10.3390/nu12061823
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Preparing and Cooking Vegetables Are Associated with Decreased Home Availability of Vegetables in Low-Income Households

Abstract: Knowing which barriers to buying and preparing/cooking vegetables at home are linked with the home availability of vegetables and how food-security status impacts this relationship will facilitate the tailoring of future public health interventions. Baseline data were used from an elementary-school-based intervention. Data on household food-security status, availability of vegetables at home, and barriers to buying and preparing/cooking vegetables were collected from 1942 parents. Differences between food-secu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 54 publications
3
34
0
Order By: Relevance
“…These findings are consistent with earlier reports that highlighted the importance of self-efficacy in improved fruit and vegetable intake [26,28]. However, the study by Landry MJ et al, [1] did not establish a significant relationship between enhanced self-efficacy and gardening activities in improving dietary intake of fruits and vegetables. Similarly, Keyte et al [29] did not establish an association between gardening at school and increased self-efficacy towards the dietary intake of fruits and vegetables.…”
Section: Relationship Between School Gardening and Self-efficacy Towasupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are consistent with earlier reports that highlighted the importance of self-efficacy in improved fruit and vegetable intake [26,28]. However, the study by Landry MJ et al, [1] did not establish a significant relationship between enhanced self-efficacy and gardening activities in improving dietary intake of fruits and vegetables. Similarly, Keyte et al [29] did not establish an association between gardening at school and increased self-efficacy towards the dietary intake of fruits and vegetables.…”
Section: Relationship Between School Gardening and Self-efficacy Towasupporting
confidence: 92%
“…Jennifer, L., Staub, D. & Colby, S [11] reported improoved self efficacy towards the intake of fruits and vegetables among the gardening group than the control group. However, Landry MJ et al, [1] did not establish the relation between enhanced self-efficacy and gardening activities in improving weekly dietary intake of fruits and vegetables. On the other hand, ealier studies by Ding et al, [12] and Gannan et al, [4] reported that home food and vegetable environment such as accesibility, availability and variety are the key determinants of the self-efficacy towards routine fruit and vegetable intake rather than school gardening activities.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…16,17 Unfortunately, many patient education programs may fail to adequately identify food insecurity levels among Evaluation of a COVID-influenced Curriculum to Address Food Insecurity in a Detroit Family Medicine Residency Clinic 22 Patients are frequently forced to make unhealthy food choices due to cost, lack of education or lack of access to nutritional food items. 12,13 Our demonstrated improvements in HbA1c levels suggest that many pre-diabetic patient's health can be improved without requiring additional diabetes medications when provided nutritional education and office visit guidance.…”
Section: Discussionmentioning
confidence: 95%
“…[9][10][11] Several additional factors influencing consumption of suboptimal dietary components as identified by clinic-based providers include perceived time constraints, food taste, impaired access to more nutritional foods and cost. 12,13 During project planning, the authors concluded with colleagues that many patients at their Michigan primary care residency clinic were consuming poorer-quality diets con-sisting of high-fat calorie laden foods with low nutrient density. During their scheduled pre-project clinic office visits, physicians had tried to routinely provide patients with basic dietary and exercise advice and brief recommendations to implement "diet and lifestyle changes" into their lifestyles as recommended in the 2015 United States Preventative Service Task Force Guidelines.…”
Section: Introductionmentioning
confidence: 99%